2011
DOI: 10.1039/c1nr10483g
|View full text |Cite
|
Sign up to set email alerts
|

Single step synthesis of graphene nanoribbons by catalyst particle size dependent cutting of multiwalled carbon nanotubes

Abstract: Graphene nanoribbons are emerging as an interesting material for the study of low dimensional physics and for the applications in future electronics due to its finite energy band gap. However, its applicability for large scale nanoelectronics may not be effectively realized unless graphene nanoribbons could be produced using a simple, viable, cost-effective and scalable technique. Here, we report the one step facile synthesis of few layered graphene nanoribbons (GNRs) by catalytically unzipping multi-walled ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…[ 70 ] The electronic structure of BN nanoribbons is much less widthdependent, [ 71 ] but edge effects can dramatically change the properties of BN nanoribbons. Graphene nanoribbons have been produced via nanotube unzipping, [74][75][76][77][78][79][80] chemical routes, [81][82][83][84] and lithography. [ 71 ] In experiment, the electrical conductivity of BN nanoribbons was measured using TEM, and high conductivity was confi rmed and explained by edge termination by oxygen atoms.…”
Section: Controlled Edge and Stacking In Bn Nanoribbonsmentioning
confidence: 99%
“…[ 70 ] The electronic structure of BN nanoribbons is much less widthdependent, [ 71 ] but edge effects can dramatically change the properties of BN nanoribbons. Graphene nanoribbons have been produced via nanotube unzipping, [74][75][76][77][78][79][80] chemical routes, [81][82][83][84] and lithography. [ 71 ] In experiment, the electrical conductivity of BN nanoribbons was measured using TEM, and high conductivity was confi rmed and explained by edge termination by oxygen atoms.…”
Section: Controlled Edge and Stacking In Bn Nanoribbonsmentioning
confidence: 99%
“…A potassium intercalation method is also used to longitudinally split the CNTs by James M. Tour [73]. Parashar et al reported a catalytic unzipping of CNTs method, based on the solubility of carbon atoms in nickel, to synthesize GNRs [70]. The GNRs are about 20-22 nm in width and consist of a single layer to a few layers of graphene.…”
Section: Top-down Methodsmentioning
confidence: 99%
“…Among them, employing the CNTs as the source to get the GNRs is mostly used in the literature because of the mature and large-scale availability of CNTs. Much effort has been dedicated to longitudinal unzipping of the CNTs, such as selective etching [59,61], chemical attacking [34,60,62,63], nanoparticle cutting [69,70] and metal atom intercalation [71,72]. In the team of James M. Tour, a simple solution-based oxidative approach using KMnO 4 and H 2 SO 4 was developed [34].…”
Section: Top-down Methodsmentioning
confidence: 99%
“…[44,45] A much more imaginative strategy is unzipping of CNTs, since a nanotube can be viewed as a folded or zipped GNR. The available routes for the reverse process cover chemical attack, [46,47] laser irradiation, [48] plasma etching, [49,50] metal-catalyzed cutting, [51,52] hydrogen treatment and annealing, [53] unzipping functionalized nanotubes by scanning tunneling microscope (STM) tips, [54] electrical unwrapping by transmission electron microscopy (TEM), [55] intercalation and exfoliation, [56,57] electrochemical unzipping, [58] and sonochemical unzipping. [59,60] Other strategies involve chemical vapor deposition (CVD) [61][62][63] and chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%